Design and development of continuous pineapple-peeling machine - Jiraporn Sripinyowanich Jongyingcharoen; Ekkapong Cheevitsopon (My University, 2022)
Importance of the work:A continuous pineapple peeler was designed having a mechanism to align the pineapple during peeling for use in small to medium-sized enterprises.Objectives: To design, fabricate and test the performance of a continuous pineapple peeler based on the physical and mechanical properties of pineapples. Materials & Methods:The physical and mechanical properties of pineapples were investigated, specifically their dimensions, the forces required to cut the ends and for peeling, and the bioyield force.A continuous pineapple-peeling machine was designed and developed.The offset of the fruit core centerline and the centerline of the cut fruit were investigated to evaluate machine performance.Results: The prototype machine consisted of four main units (cutting, gripping, peeling and pneumatic control).The most important part of the design was the V-shaped grippers angled at 90° that were driven by a rack and pinion mechanism.The machine could hold pineapples of various diameters with the axis of the pineapple aligned with the movement of a tubular knife.During operation, the pineapple ends were first removed by a cutting unit.Then, the grippers held the pineapple horizontally while it was peeled by the unit's tubular knife.From performance testing, the prototype machine had a peeling capacity of approximately 530 fruits/h, with an effectiveness of 98.2%.Main finding: With the mechanism to align the pineapple during peeling developed in this study, the continuous pineapple-peeling machine had high peeling capacity and high effectiveness, making it acceptable by fresh pineapple processors.
Keywords: Pineapple and bromelain studies